2006
DOI: 10.1021/jp0565150
|View full text |Cite
|
Sign up to set email alerts
|

Sum Frequency Generation Study of the Room-Temperature Ionic Liquids/Quartz Interface

Abstract: The purpose of this investigation is to study the ionic liquid/quartz interface with sum frequency generation vibrational spectroscopy (SFG). SFG spectroscopy was chosen for this study because of its unique ability to yield vibrational spectra of molecules at an interface. Different polarization combinations are used, which probe different susceptibilities, giving SFG the ability to determine molecular orientation at the interface. The ionic liquids used were 1-butyl-3-methylimidazolium tetrafluoroborate, [BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
182
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(204 citation statements)
references
References 55 publications
(96 reference statements)
17
182
5
Order By: Relevance
“…26 Similar gauche defect reduction was seen in SFG studies of short-to long-chain 1-alkyl-3-methylimidazolium salts at the SiO 2 interface. 116,117 The structure of the IL-vacuum interface for ͓emim͔ + / NO 3 − was reported by Yan et al 119 Surface tension and thickness of IL-vapor interfaces have been reported from both simulations 120 and experiment. 121 By accounting for both capillary waves and zero-point motions, the underlying structure of the IL surface has been determined by comparing MD simulations with x-ray reflectivity experiments.…”
Section: Il Interfacesmentioning
confidence: 75%
See 1 more Smart Citation
“…26 Similar gauche defect reduction was seen in SFG studies of short-to long-chain 1-alkyl-3-methylimidazolium salts at the SiO 2 interface. 116,117 The structure of the IL-vacuum interface for ͓emim͔ + / NO 3 − was reported by Yan et al 119 Surface tension and thickness of IL-vapor interfaces have been reported from both simulations 120 and experiment. 121 By accounting for both capillary waves and zero-point motions, the underlying structure of the IL surface has been determined by comparing MD simulations with x-ray reflectivity experiments.…”
Section: Il Interfacesmentioning
confidence: 75%
“…A wide variety of experimental, theoretical, and simulation methods have been applied to the study of ILs at interfaces. [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] Santos and Baldelli 112 have used interfacial sumfrequency generation ͑SFG͒ to show that at IL interfaces with gases or vacuum, alkyl chains on either the cations or the anions extend from the surface into the gas or vacuum. Rutherford backscattering spectra for the ͓bmim͔ + / ͓PF 6 ͔ − -vacuum interface also show the cation butyl group protruding from the bulk liquid into vacuum.…”
Section: Il Interfacesmentioning
confidence: 99%
“…These results are consistent with surface spectroscopic and diffraction data. [103][104][105][106][107] Interfaces with crystals are known to induce structural order of liquids, 108 and in the case of ILs, spectroscopy results have been reported at the quartz, 109 silice, 110 and platinum charged interfaces, 111 revealing specific ordering of the imidazolium cations. 112 At the surface of a platinum electrode, the cation's ring orients rather parallel to the surface in response to the negative surface charge.…”
Section: Discussionmentioning
confidence: 99%
“…When the silver electrode was negatively charged some imidazolium ring vibrational modes and some N-CH 3 vibrations were enhanced, suggesting that the imidazolium rings were parallel to the surface [81]. This seems to be the case also in other systems such as [C 4 6 ], 1-methylimidazole, and 1-butylimidazole, studied by Raman spectroscopy, and with depolarization ratios recorded from 2700 to 3300 cm À1 [82]. Mixed systems of organic molecules and ionic liquids that form separate phases (by thermomorphic phase separation) have been also studied by Raman spectroscopy [83].…”
Section: N]mentioning
confidence: 97%